Tumor T1 Relaxation Time for Assessing Response to Bevacizumab Anti-Angiogenic Therapy in a Mouse Ovarian Cancer Model. - Murali K Ravoori; Masato Nishimura; Sheela P Singh; Chunhua Lu; Lin Han; Brian P Hobbs; Sunila Pradeep; Hyun J Choi; James A Bankson; Anil K Sood; Vikas Kundra (PLoS ONE, 2015)
To assess whether T1 relaxation time of tumors may be used to assess response to bevacizumab anti-angiogenic therapy.12 female nude mice bearing subcutaneous SKOV3ip1-LC ovarian tumors were administered bevacizumab (6.25ug/g, n=6) or PBS (control, n=6) therapy twice a week for two weeks. T1 maps of tumors were generated before, two days, and 2 weeks after initiating therapy. Tumor weight was assessed by MR and at necropsy. Histology for microvessel density, proliferation, and apoptosis was performed.Bevacizumab treatment resulted in tumor growth inhibition (p<0.04, n=6), confirming therapeutic efficacy. Tumor T1 relaxation times increased in bevacizumab treated mice 2 days and 2 weeks after initiating therapy (p<.05, n=6). Microvessel density decreased 59% and cell proliferation (Ki67+) decreased 50% in the bevacizumab treatment group (p<.001, n=6), but not apoptosis.Findings suggest that increased tumor T1 relaxation time is associated with response to bevacizumab therapy in ovarian cancer model and might serve as an early indicator of response.